Characterization of novel L-asparaginases having clinically safe profiles from bacteria inhabiting the hemolymph of the crab, Scylla serrata (Forskål, 1775) - Lailaja, V P; Sumithra, T G; Reshma, K J; Anusree, V N; Amala, P V; Kishor, T G; Sanil, N K (Folia microbiologica, 2022)
L-asparaginase (ASNase) is the principal chemotherapeutic agent against different blood cancers. The risks associated with current clinical preparations demand screening for novel ASNases. Accordingly, the study was conducted to shortlist ASNases having clinically safer profiles from a novel niche, namely, microbes in the gut and hemolymph of apparently healthy Scylla serrata. A four-step strategic approach incorporating the essential requirements for clinically safer profiles was followed. The initial step through plate assay showed five (9.61%) potential ASNase producers. The relative prevalence of ASNase producers was higher in hemolymph (13.33%) than gut (4.5%). The positive isolates were identified as Priestia aryabhattai, Priestia megaterium, Bacillus altitudinis, Shewanella decolorationis, and Chryseomicrobium amylolyticum. Quantitative profiles revealed high ASNase production (114.29 to 287.36 U/mL) without any optimization, with an added advantage of the extracellular production. The second step for substrate specificity studies revealed the absence of L-glutaminase and urease activities in ASNases from C. amylolyticum and P. megaterium, the most desirable properties for safe clinical applications. This is the first report of glutaminase and urease-free ASNase from these two bacteria. The third step ensured type II nature of selected ASNases, the targeted form in clinical applications. The fourth step confirmed the activity and stability in human physiological conditions. Altogether, the results revealed two potential ASNases with clinically compatible profiles.
Keywords: hemolymfa; Bacteria; Antineoplastic Agents; Animals; lidé; krabi; glutaminasa; Hemolymph; protinádorové látky; Brachyura; zvířata; Humans; Asparaginase; asparaginasa; Glutaminase